Thoughts on the evolution and extinction of Cretaceous ammonites - Kennedy, W (1989)
Problems that beset the worker on Cretaceous ammonites - chronostratigraphic, biostratigraphic and evolutionary - are reviewed, and examples of evolutionary patterns noted. Problems of stratigraphic nomenclature are illustrated by the base of the Turonian stage. The possible lengths of ammonite zones is considered for the Upper Cenomanian and Campanian. Provincialism is discussed in relation to the Vascoceratinae. The various types of dimorphism are illustrated. Case histories are used to show examples of stasis, phyletic evolution, divergence, convergence, possible iterative evolution, and heterochrony. The patterns of decline and extinction at the end of the epoch are documented quantitatively, and it is suggested that Nautilus owes its survival to a different reproductive strategy to that of both ammonites and belemnites. -Author